A Legal Aspect on the Development of Environmental Concept Management in Aceh Barat District - Nila Trisna (Proceedings of AICS - Social Sciences, 2017)
The development of environmental concept is a sustainable development, which optimally takes advantage on natural and human resources by synchronizing human activities with the sources of natural resources for monitoring and environmental sources. As the implementation of the Environmental Act, it is expected to be similar with its real condition. In terms of keeping environment sustainability, the implementation of the Environmental Act is very effective in improving environment quality in a state. The eco development in Aceh Barat District is expected to be able to respect on environment by more focusing on ethics and the knowledge on environment in a view that is held by people and government. The research shows that in the sustainable development, the Government of Aceh Barat has made an effort in accordance with the Act of Environment but due to the limit of human resources and tools that are not able to support the program has caused the environment development that is having orientation on environment becomes a hurdle and it is prone to be stopped. Based on the fact above, this research poses two problems are: 1. How is the effort of Aceh Barat in realizing the management of environmental development with the concept of environment? 2. How is the implementation of the Act of Environment in Aceh Barat District? This research applies descriptive analysis, it is expected might be able to describe and analyze a phenomenon that exists in the reality. The method applied is by juridical empirical research approach. The effective management system of environment needs to be developed seriously and effective based on environmental law.